High PEEP in ARDS: A Double-Edged Sword? Analyzing Oxygen Improvement Versus Reduced Tissue Oxygen Delivery: A Systematic Review and Meta-Analysis - Kaur, Ravinder; Rani, Poonam; Singh, Amandeep; Aggarwal, Reema; Kumar, Pankaj (Journal of Neonatal Surgery, 2025)
Background: High positive end-expiratory pressure (PEEP) is commonly employed in managing acute respiratory distress syndrome (ARDS) to improve oxygenation and prevent alveolar collapse. However, the impact of high PEEP on overall oxygen delivery, cardiac output, and patient mortality remains controversial. This systematic review and Meta-analysis aims to evaluate available evidence on the benefits and drawbacks of high PEEP in ARDS, particularly focusing on the trade-off between improved arterial oxygenation and compromised tissue oxygen delivery Methods: We systematically reviewed and analyzed clinical trials, observational studies, and computational modeling studies assessing the effects of high PEEP on arterial oxygenation, cardiac output, and tissue oxygen delivery in ARDS patients. A comprehensive search was conducted in PubMed, MEDLINE, Embase, and Cochrane Library from inception to March 2024. Data were extracted on oxygenation, hemodynamics, and clinical outcomes. Meta-analysis was performed using a random-effects model. Results: High PEEP significantly improved arterial oxygenation (pooled mean increase in PaO₂: 6.3 kPa [95% CI: 5.6–7.0], p < 0.001). However, tissue oxygen delivery was consistently reduced due to compromised cardiac output (pooled mean reduction: 19% [95% CI: -15% to -23%], p < 0.001). The pooled mortality risk ratio was 0.97 (0.86-1.10), indicating no significant effect on mortality and with notable inconsistencies across trials. Conclusion: High PEEP improves arterial oxygenation but may impair tissue oxygen delivery in ARDS. Clinicians should balance the benefits of improved gas exchange against the potential risks of reduced perfusion when setting PEEP levels. Individualized PEEP titration may optimize outcomes.